Analisa Pengaruh Jumlah Penerima dan Penyaluran Pinjaman melalui Finansial Teknologi (fintech) terhadap Pertumbuhan Ekonomi Masyarakat melalui Regresi Linear - Sri Farida Utami; Willy Prihartono; Mohamad Alif Dzikry (Ikatan Ahli Informatika Indonesia, 2024)
This study looks into the relationship between the number of loans received and the amount funnelled by the technology financial platform and the economic growth of a population. Fintech. The method used in this study is linear regression. In recent years, fintech has grown to be a significant component of the financial system, particularly in emerging nations like Indonesia where traditional financial services are still unavailable. The study begins with the hypothesis that fintech can improve financial inclusion; theoretically, this will raise economic growth by improving the distribution of financial resources and the ease with which credit can be obtained. Important variables that were examined in the study were the total number of borrowers, the distribution of loans overall, and measures of economic growth. The outcomes of the linear regression demonstrated a strong positive association between the quantity of borrowing, the availability of fintech loans, and the population's economic expansion. The report emphasizes the significance of rules that enable healthy and inclusive fintech growth and offers pertinent policy implications for decision-makers and players in the fintech industry. The study's finding supports the claim that, by facilitating better access to credit and a more fair distribution of credit, fintech may significantly contribute to economic growth. According to the report, in order to maximize fintech's beneficial effects on the economy, policies that foster its growth are necessary.